Sixteen for '16 : a progressive agenda for a better America - Babones, Salvatore J. (Policy Press shorts. Insights., 2015)
The progressive movement is on the march in America and this accessible book points toward a destination. Sixteen for '16 offers a new agenda for the 2016 US election crafted around sixteen core principles that all progressives can believe in, from securing jobs to saving the Earth. Decades of destructive social, economic, and political policies have devastated poor, working, and even middle class American communities. It is now clear to everyone that the emperor has no clothes, that harsh austerity does not bring prosperity, and that the wealthy have no intention to see their wealth trickl.